Effects of dietary phytol on tissue accumulation of phytanic acid and pristanic acid and on the tissue lipid profiles in mice. (2nd July 2020) - Nakanishi, Tomonori; Kagamizono, Kazuhiro; Yokoyama, Sayaka; Suzuki, Ryoji; Sakakibara, Hiroyuki; Erickson, Laurie; Kawahara, Satoshi
Abstract: Recent in vitro evidence suggests that the phytol‐derived fatty acids, phytanic acid (PA) and pristanic acid (PrA), are components of animal products with the potential to cause both beneficial and harmful effects on human health. In this study, we investigated the in vivo tissue accumulation of PA and PrA and the changes in tissue lipid profiles, using mice fed a phytol‐containing diet. After 4 weeks of treatment with a diet containing 1.0% phytol, plasma, adipose tissue, liver, and brain were collected and their lipid profiles were biochemically and gas‐chromatographically determined. Dietary phytol caused PA and PrA accumulation in the adipose tissue and liver but not in the brain, and reduced plasma and liver triacylglycerol levels. Phytol intake also decreased the fatty acid concentrations in the adipose tissue, especially polyunsaturated fatty acids such as linoleic acid, but increased the concentrations of these fatty acids in the liver. However, dietary phytol had a low impact on the brain lipid profile. This study suggests that dietary phytol intake caused accumulation of PA and PrA and modified lipid profiles in the adipose tissue and liver, but that the brain is an insusceptible tissue to dietary phytol‐induced changes.